Analysis of body constitutions discrimination based on radial pulse wave by SVM. (24th October 2022) - Li, Nan; Yu, Jiarui; Mao, Xiaobo; Zhao, Yuping; Huang, Luqi
In this work, a new method for distinguishing human's physical constitution based on pulse information is proposed. Firstly, pulse data were collected, processed and pulse cycles were segmented. Secondly, time domain features, features coefficients, power spectrums and energy values of pulse wave were extracted and analysed, respectively. Finally, pulse features were evaluated and classified to distinguish different body constitutions by SVM classifier. The experiment indicated that the features selected could be appropriately used to analyse the physical constitutions and can serve as the basis for research on constitution assessment based on traditional Chinese medicine pulse diagnosis.